Experimental analysis on the mooring lines force behaviour of semi-submersible in regular waves - Khairuddin, N. M. (Penerbit UTM, 2014)
The effect of the mooring line force of a typical semi-submersible with square column under regular sea waves for wave heading condition is reported in this paper. A 1:81 scale model of 58748 M.Tonne moored semi-submersible was tested in Marine Technology Towing Tank of Universiti Teknologi Malaysia with 120 m in length, 4 m in width and 2.5 m in depth for the wave frequency from 0.4297 Hz to 1.7189 Hz in steps of 0.1433 Hz. In the tests, model was moored horizontally that are attached to the structure above the water surface level in the head sea with four linear springs forward and aft. Such a system does not have practical usage but is used to study the loading and response of the semi-submersible in the absence of the catenary mooring lines The force or tensions on the mooring lines was measured by load cells. The force measured by the load cells were analyzed to obtain the behavior of the mooring lines force at every frequency step. From the analysis of the experimental results, it is found that among the forward and aft mooring lines, the tension in forward mooring lines is 2 to 4 times more than the tension in aft mooring lines. The mooring forces are not equally shared by forward and aft mooring lines. It also showed that the behavior of all mooring lines forces at each column have a similar trend along the frequency.